Freedom of Expression and Spreading Religious Hatred: Perspectives from International Law - Abolfazl JAFARI-SALES; Vahid DEHGHANPOUR; Mir Mohammad Ali SEYYED JALILI KOHKAMAR; Taha ESLAMI; Erfan KIANI; Mohammad MEHRIROKH; Poya SAFARISANI; Faezeh Sadat SEYYED BAGHERI KOHKAMAR (Košická bezpečnostná revue, 2025)
Freedom of expression is a fundamental human right that allows individuals to express their thoughts, opinions, and beliefs freely. However, this right is not absolute and may be limited to prevent harm or protect the rights and reputation of others. One area of concern is the spread of religious hatred, which can lead to social unrest, discrimination, and violence. This review article explores the complex relationship between freedom of expression and the spread of religious hatred from the perspectives of international law. By examining international legal frameworks, this paper aims to provide insights into the delicate balance between protecting freedom of expression and preventing the incitement of religious hatred.